Seasonal variation of 25-Hydroxyvitamin D and indices of carbohydrate and lipid metabolism in postmenopausal women - Huta-Osiecka,Anna; Wochna,Krystian; Kasprzak,Zbigniew; Nowak,Alicja (PeerJ, 2021)
Background Some studies indicate vitamin D’s significant contribution to metabolic processess. Therefore, the purpose of this study was to evaluate the level of carbohydrate and lipid metabolism indices in relation to seasonal changes in 25-hydroxyvitamin D (25(OH)D) concentration in postmenopausal women. Methods Sixteen postmenopausal women meeting health criteria and not using vitamin D supplementation were included in the study. Seasonal variation of somatic features and the serum concentration of 25(OH)D, glucose, insulin, parathormon, sclerostin and lipid profile were determined on two terms (autumn-winter). Results Comparative analysis of the variables between the study terms revealed a marked decrease in the concentration of 25(OH)D (p ≤ 0.0001), insulin (p < 0.05), insulin resistance index (HOMA-IR), (p < 0.05). The significant positive correlations of changes (Δ) between autumn and winter in 25(OH)D with body mass (p < 0.05), and fat mass (p ≤ 0.01), measured in the first study term, in the group of women with normal body mass index (BMI), and negative correlation with fat mass (p < 0.05) in women with a BMI value above the reference values, were found. The relationship analysis showed that in women with normal BMI, the decrease in 25(OH)D concentrations was greater when the body fat percentage was higher, whereas in women with a BMI value above the reference values, the higher the fat percentage, the smaller was the decrease in 25(OH)D concentration. Conclusions Seasonal changes in 25(OH)D concentration did not significantly affect the concentration of carbohydrate and lipid metabolism indices. The magnitude of decline in 25(OH)D levels depends on the fat mass. We suppose that environmental or lifestyle-related factors, e.g., nutritional behaviours, may have had more influence on metabolic indices than changes in 25(OH)D.
Keywords: Vitamin D; Fat mass; Insulin sensitivity; Lipid profile; Postmenopausal women; Seasonal variation